2018
DOI: 10.4236/jep.2018.911073
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Integrated Coastal Vulnerability Index for the Ivorian Coast in West Africa

Abstract: This study assesses the vulnerable state of the 566-km Ivorian coastal area using the physical (geomorphology, coastal slope, coastal retreat rate, relative sea level rise and wave/Tide energy) and socioeconomic (coastal population density, harbor, airport, road, land use and protected area) factors as indicators. This enabled an Integrated Coastal Vulnerability Index to be determined for the Ivorian coastal zone. This Index could be defined as the weighted average of indexes based on physical and socioeconomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 12 publications
2
31
0
Order By: Relevance
“…The coastline is dynamic and is, therefore, an area of constant change. The changes depend on geology and geomorphology; the natural processes such as tidal, swell and wind sea waves exacerbated by sea-level rise [1] and annual rainfall change [2]. The changes of the coastline also depend largely on human activities such as urbanization, ports defense construction, removal of sand and vegetation and construction of barrage [3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The coastline is dynamic and is, therefore, an area of constant change. The changes depend on geology and geomorphology; the natural processes such as tidal, swell and wind sea waves exacerbated by sea-level rise [1] and annual rainfall change [2]. The changes of the coastline also depend largely on human activities such as urbanization, ports defense construction, removal of sand and vegetation and construction of barrage [3].…”
Section: Introductionmentioning
confidence: 99%
“…This The study carried out by [11], based on processes (relative sea-level rise, tidal range, and wave height) and state factors (geomorphology, coastal slope, and coastline change rate) showed that vulnerability of the Ivorian coastal section increases eastward and, depends strongly on geomorphology and swell wave energy coming from southern Atlantic. More recently, [1] [12] that resulted in reduced flows of almost all the rivers [13]. Moreover, the majority of these rivers have been dammed mostly for energy and irrigation purposes, resulting in significant alteration of their hydrology and Table 1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, MCDM strategies are divided into Multi-Objective decision making (MODM) and Multi-Attribute decision making (MADM). The most distinction between the two teams of strategies is predicated on the determination of alternatives (Tano et al 2018;Tahri et al 2017). In MODM, additionally referred to as multi objective programming or a vector optimization / maximization / step-down drawback, the alternatives don't seem to be preset however instead a collection of objective functions is optimized subject to a group of constraints.…”
Section: Multi-criteria Decision Making (Mcdm)mentioning
confidence: 99%
“…Canada; Doukakis (2005) for Greece; Coelho et al, (2006) for west coast of Portugal; Yin et al, (2012) for China; Kumar et al, (2010) for India; Ozyurt and Ergin (2010) for Turkey; Duriyapong and Nakhapakorn (2011) for Thailand; Addo (2013) for Ghana; Zanetti et al, (2016) for Brazil; Wahab (2017) for Malaysia; Tano et al, (2018) for Ivorian coast, west Africa and Kantamaneni et al, (2018) for some cities in UK, etc. Not many detailed studies were carried out on coastal vulnerability of the Arab coastal region.…”
Section: Literature Reviewmentioning
confidence: 99%